REFLEKSI MAHASISWA PGSD USWIM NABIRE PAPUA TENGAH TERHADAP PENTINGNYA PERLINDUNGAN ANAK DALAM MEMBANGUN DISIPLIN POSITIF DI KELAS - Semi Gobai; Albertina Petege; Rani Simon Sarira; Sartika Vera Doli Mofu; Wafiq Azizah Maharani; Akas Gresela Wakole; Jermanto Subeno Lasamahu (STKIP Pesisir Selatan, 2026)
Child protection in primary education has become an important issue because punitive disciplinary practices that potentially hinder students’ psychological and social development are still commonly found, including in Central Papua. This study aims to analyze the reflections of PGSD USWIM Nabire students regarding the importance of child protection in building positive discipline in the classroom. The study employed a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, observations, and documentation involving 15–20 purposively selected students, and were analyzed using thematic analysis techniques. The findings indicate that students have a relatively high level of reflection on the importance of child protection, marked by their understanding of physical, psychological, and emotional aspects, as well as positive perceptions toward discipline based on a humanistic approach. However, there remains a gap between conceptual understanding and practical implementation abilities, along with challenges such as a harsh disciplinary culture, limited facilities, and lack of training. This study confirms that student reflection plays an important role in shaping prospective teachers’ readiness to create safe, inclusive, and child-friendly learning environments. The findings also highlight the need to strengthen teacher education curricula based on reflective practice so that students are not only able to understand the concept of child protection, but also capable of applying it contextually in elementary school learning.